Police infiltration in Spain as an investigative measure for fighting corruption - Adán Carrizo González-Castell (Revista Brasileira de Direito Processual Penal, 2017)
The present paper addresses the concept of police infiltration, as well as the necessity of its use for fighting corruption and organized crime. In doing so, we analyze not only Spanish law, but also existing international legislation in the European Union, with particular emphasis on international cooperation in this field.